(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
This study aimed to evaluate the effects of black cumin seed (BCS) supplementation on intestinal morphology and growth performance in broiler chickens during the finishing period. A total of 225 one-day-old Lohman meat (Indian River) broiler chicks, with an average body weight of 40±0.50 g, were divided into five groups, with three replicates of 15 birds each. The treatments were T0 = control (basal feed), T1 = basal feed + antibiotic, T2 = basal feed + 0.5% BCS, T3 = basal feed + 1% BCS, and T4 = basal feed + 1.5% BCS. Birds were reared under standard management for 35 days, during which growth performance parameters (body weight, feed intake, feed conversion ratio) were recorded weekly. At the end of the trial, three broilers from each group were randomly necropsied, and samples of the small intestine (duodenum, jejunum, and ileum) were fixed with 10% neutral buffered formalin solution and stained with Hematoxylin and Eosin (H&E). The results indicated that average body weight gain, feed intake, and feed conversion ratio significantly improved with dietary inclusion of 1% and 1.5% BCS compared with the control and antibiotic groups. The dietary treatments influenced the morphology of small intestinal villi. Birds fed with 1.5% BCS presented higher villus height (duodenum, jejunum, ileum), villus surface area (duodenum), and villus height  crypt depth (duodenum, jejunum, ileum) compared with control and other treatment groups (p<0.05). In the duodenum, total goblet cell count was higher (p<0.05) in all of the supplemented groups when compared with non-supplemented birds. Moreover, supplementation with 1.5% significantly decreased epithelial thickness and the number of intestinal goblet cells compared with other supplemented and control treatments (p<0.005). These findings suggest that dietary supplementation with 1.5% BCS has a beneficial effect on intestinal morpho-physiology of broilers grown at normal conditions in an open-sided environment. Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 79-89